2017
DOI: 10.1161/circoutcomes.116.003651
|View full text |Cite
|
Sign up to set email alerts
|

Disparity Between Indications for and Utilization of Implantable Cardioverter Defibrillators in Asian Patients With Heart Failure

Abstract: Background-Implantable cardioverter defibrillators (ICDs) are lifesaving devices for patients with heart failure (HF) and reduced ejection fraction. However, utilization and determinants of ICD insertion in Asia are poorly defined. We determined the utilization, associations of ICD uptake, patient-perceived barriers to device therapy and, impact of ICDs on mortality in Asian patients with HF. Methods and Results-Using the prospective ASIAN-HF (Asian Sudden Cardiac Death in Heart Failure) registry, 5276 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 43 publications
4
54
0
Order By: Relevance
“…47,48 This difference is likely related to differences in reimbursement; a separate study from ASIAN-HF showed that on a country level, there was a strong association between device usage and out-of-pocket pay. 49 Significant differences in mortality were seen in the PARADIGM-HF trial; patients from LA [10 (95% confidence interval-CI 9-11) deaths per 100 patient-years] and AP [9 (95% CI 8-10) deaths per 100 patient-years] had worse mortality compared to WE [7 (95% CI 6-8) deaths per 100 patient-years] independent of differences in clinical characteristics ( Table 1). 8 Regional variations in clinical outcome are more pronounced when looking at hospitalization for HF.…”
Section: Overall Clinical Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…47,48 This difference is likely related to differences in reimbursement; a separate study from ASIAN-HF showed that on a country level, there was a strong association between device usage and out-of-pocket pay. 49 Significant differences in mortality were seen in the PARADIGM-HF trial; patients from LA [10 (95% confidence interval-CI 9-11) deaths per 100 patient-years] and AP [9 (95% CI 8-10) deaths per 100 patient-years] had worse mortality compared to WE [7 (95% CI 6-8) deaths per 100 patient-years] independent of differences in clinical characteristics ( Table 1). 8 Regional variations in clinical outcome are more pronounced when looking at hospitalization for HF.…”
Section: Overall Clinical Characteristicsmentioning
confidence: 99%
“…In addition, advanced HF therapies, including left ventricular assist devices and heart transplantation, are still very limited in most low‐middle‐income countries compared to WE and NA . This difference is likely related to differences in reimbursement; a separate study from ASIAN‐HF showed that on a country level, there was a strong association between device usage and out‐of‐pocket pay …”
Section: Regional Differences In Heart Failurementioning
confidence: 99%
See 3 more Smart Citations